REPRODUCTIVE OUTCOMES IN WOMEN WITH AUTOIMMUNE THYROIDITIS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Autoimmune thyroiditis (AIT), commonly referred to as Hashimoto’s thyroiditis, is a chronic immune-mediated disorder characterized by progressive destruction of thyroid tissue, often resulting in hypothyroidism. Women of reproductive age are predominantly affected, and AIT has been associated with reduced fertility and adverse pregnancy outcomes. This review examines the mechanisms by which autoimmune thyroiditis influences reproductive health, including hormonal dysregulation, menstrual disturbances, ovulatory dysfunction, diminished oocyte quality, and increased risks of miscarriage and preterm delivery. Diagnostic strategies, including evaluation of thyroid hormone levels and thyroid autoantibodies, are discussed, alongside therapeutic approaches with emphasis on levothyroxine replacement therapy. The role of assisted reproductive technologies (ART), particularly in vitro fertilization (IVF), is analyzed, highlighting the importance of achieving euthyroidism and monitoring thyroid autoantibody titers. Evidence indicates that timely diagnosis and proper management significantly improve reproductive outcomes in women with autoimmune thyroiditis.
Keywords: Hashimoto’s thyroiditis, hypothyroidism, autoimmune thyroiditis, fertility, reproductive health, menstrual irregularities, ovulatory dysfunction, thyroid autoantibodies, in vitro fertilization